Corporate social responsibility and workplace health promotion: A systematic review - Alonso-Nuez, María-Jesús; Cañete-Lairla, Miguel-Ángel; García-Madurga, Miguel-Ángel; Gil-Lacruz, Ana-Isabel; Gil-Lacruz, Marta; Rosell-Martínez, Jorge; Saz-Gil, Isabel (Frontiers in Psychology, 2022)
The complex situation that global society is facing as a result of Covid-19 has highlighted the importance of companies committing to the principles of social responsibility. Among the internal initiatives, those related to the health of workers are, obviously, highly topical. The objective of our research is to provide concise knowledge of the relationship between workplace health promotion (WHP) and corporate social responsibility (CSR) so that the relevant specialized research was gathered in a single document that lays the foundations of its applicability. A systematic review, following the PRISMA method, has been carried out. Twenty-seven articles have been selected from the main scientific databases. Their qualitative analysis concludes that CSR and WHP are linked, have beneficial reciprocal effects, need committed leadership respectful of autonomy and voluntariness, and require the establishment of specific goals within the framework of the organizations' sustainability policies. Future studies should establish the impact of the pandemic on these aspects.